2023
DOI: 10.1039/d2fo02877h
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin relieves oxaliplatin-induced pain by affecting TLR4/NF-κB inflammatory signaling and the gut microbiota

Abstract: Diosgenin extracted from fenugreek, yam and other foods has a wide range of pharmacological activities especial for the treatment of pain and other nervous system diseases. However, its role in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This, diosgenin has neuroprotective and antioxidant activity, modulates neurotransmitters, is antiapoptotic and anti-inflammatory, attenuates Ca 2+ influx modulating neurotrophic factors, inhibits tau phosphorylation, and can regenerate neural networks (Sun et al, 2015). Some of these activities may well stem from the repression of TNF-α, IL-1β, and IL-6 levels and the NF-κB pathway (Zhang et al, 2017;Man et al, 2023) in addition to the aforementioned actions. Because of these diverse properties, diosgenin can generate mnemonic/ antidepressant/anxiolytic outcomes in our behavioral paradigms following SPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This, diosgenin has neuroprotective and antioxidant activity, modulates neurotransmitters, is antiapoptotic and anti-inflammatory, attenuates Ca 2+ influx modulating neurotrophic factors, inhibits tau phosphorylation, and can regenerate neural networks (Sun et al, 2015). Some of these activities may well stem from the repression of TNF-α, IL-1β, and IL-6 levels and the NF-κB pathway (Zhang et al, 2017;Man et al, 2023) in addition to the aforementioned actions. Because of these diverse properties, diosgenin can generate mnemonic/ antidepressant/anxiolytic outcomes in our behavioral paradigms following SPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in accordance with the fact that in vivo treatment in mice with the phytosteroid diosgenin reversed oxaliplatininduced peripheral neuropathy parameter values (e.g., mechanical withdrawal threshold and cold hyperalgesia). Again, treatment of the animals with FMT indicated that the pain ameliorating effect of diosgenin is GM-dependent [138].…”
Section: Trauma-induced Neuropathic Painmentioning
confidence: 95%
“…In another study in mice, it was proven that diosgenin, a steroid sapogenin found in fenugreek seeds and yam, could exert an analgesic effect in oxaliplatin-induced pain. The analgesic effect can be attributed to its influence on the TLR-4/NF-jB inflammatory signalling pathway [74].…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%